Effects of Nitrogen Application on Post‐Silking Root Senescence and Yield of Maize. (1st May 2015) - Chen, Yanling; Zhang, Jie; Li, Qian; He, Xiaolong; Su, Xiaopo; Chen, Fanjun; Yuan, Lixing; Mi, Guohua
Abstract : The size of roots and their physiological activity during the grain‐filling stage affect water and nutrient uptake, and grain yield (GY) in maize ( Zea mays L.). The aim of this study was to determine the effects of different N levels on postanthesis root senescence in field‐grown maize. Three N levels (0, 120, 240 kg N ha −1 ) was applied to field‐grown maize, and the length and weight of roots in the 0‐ to 40‐cm soil layer, nitrogenous compounds in xylem sap, N uptake, dry matter (DM), N accumulation, and GY were analyzed. Shoot N accumulation, but not grain yield, was higher in the N240 treatment than in the N120 treatment. At the silking stage, the root length was longest in the N0 treatment and shortest in the N240 treatment. This was because of the high root/shoot (R/S) and root C/N ratios in N0. Total root length decreased throughout the grain‐filling period, mainly because of the reduced length of early developed nodal roots. The root length decreased by 27% in the N0 treatment, to a smaller extent compared to that in N120 (52%) and N240 (51%). The amounts of NO3 − –N, NH4 + –N and amino acid‐N in the xylem sap were highest in the N240 treatment during the entire grain‐filling stage, suggesting that a high N supply increased root N‐uptake activity. Based on these results, we conclude that high root N‐uptake activity, not delayed root senescence, resulted in the large accumulation of N in the shoot under excess N.